2022
DOI: 10.1111/jmwh.13400
|View full text |Cite
|
Sign up to set email alerts
|

Midwifery Autonomy and Employment Changes During the Early COVID‐19 Pandemic

Abstract: Introduction:The COVID-19 pandemic presented the midwifery workforce with challenges for maintaining access to high-quality care and safety for patients and perinatal care providers. This study analyzed associations between different types of professional autonomy and changes in midwives' employment and compensation during the early months of the pandemic.Methods: An online survey distributed to midwifery practices in fall 2020 compared midwives' employment and compensation in February 2020 and September 2020.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Published disaster plans that focused on perinatal care during an extended viral pandemic did not exist at the onset of COVID‐19. In particular, available recommendations dealing with infectious disease failed to consider the special needs of pregnant women and newborns 11 . Guidelines developed in the aftermath of Hurricane Katrina contained detailed advice for governmental and health organizations to plan and prepare for perinatal care in an emergency 22 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Published disaster plans that focused on perinatal care during an extended viral pandemic did not exist at the onset of COVID‐19. In particular, available recommendations dealing with infectious disease failed to consider the special needs of pregnant women and newborns 11 . Guidelines developed in the aftermath of Hurricane Katrina contained detailed advice for governmental and health organizations to plan and prepare for perinatal care in an emergency 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Full survey methodology and quantitative findings have been published elsewhere. 11 ✦ Providing care during the COVID-19 pandemic proved stressful and demanding for midwifery practice directors, with regulations, institutions, team dynamics, and financial logistics driving most of the changes that occurred in midwifery practices.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been recognized as the "gold standard" 9 for midwifery workforce prediction and has been proven to be very effective when applied in the National Health Systems of the United Kingdom 10 . Full-time equivalent (FTE) midwives, defined as the proportion of midwifery service hours per midwife in the maternity ward, have been applied in other research for employment changes or human resources 11,12 . Therefore, the aim of this study was to adopt the BR + method to investigate midwifery workforce shortage in the midwifery settings in China.…”
Section: Introductionmentioning
confidence: 99%
“…Although community births continue to represent less than 2% of the total number of births in the United States, the rate of home birth rose by 23.3% from 2019 to 2020 2 and by an additional 12% from 2020 to 2021 3 . Authors who surveyed midwifery and obstetric care providers during the early months of the pandemic found that the largest staffing and work hour increases occurred among midwives in community birth settings, compared with midwives and obstetricians in hospital settings 4,5 . Based on Google search data, interest in home birth remains significantly elevated from prepandemic levels 6 .…”
Section: Introductionmentioning
confidence: 99%